2001
DOI: 10.1093/clinchem/47.7.1157
|View full text |Cite
|
Sign up to set email alerts
|

Glycohemoglobin: A Primary Predictor of the Development or Reversal of Complications of Diabetes Mellitus

Abstract: Background: Diabetes mellitus is a major health problem worldwide with long-term micro- and macrovascular complications responsible for a majority of its morbidity and mortality. The development and progression of these complications relate strongly to glycemic control. Methods: We reviewed the literature extensively for studies that relate glycemic control to the development and progression of diabetic complications. We discuss the problems of standardizing glycohemoglobin measurements for moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 57 publications
1
57
1
2
Order By: Relevance
“…Because of their high reactivity, these compounds are suspected to play a role in the development and progression of late diabetic complications. Already in 2001, haemoglobin, albumin and myosin were described as glycated [34][35][36]. Ahmed et al [37] reported on an up to ten-fold increase in protein glycation and oxidation-free adducts in the blood of diabetic patients, and an up to 15-fold increase in urinary excretion.…”
Section: Glycationmentioning
confidence: 99%
“…Because of their high reactivity, these compounds are suspected to play a role in the development and progression of late diabetic complications. Already in 2001, haemoglobin, albumin and myosin were described as glycated [34][35][36]. Ahmed et al [37] reported on an up to ten-fold increase in protein glycation and oxidation-free adducts in the blood of diabetic patients, and an up to 15-fold increase in urinary excretion.…”
Section: Glycationmentioning
confidence: 99%
“…Prevention of complications specific to diabetes is a key issue because of the morbidity and mortality associated with the disease (4). Clinically significant morbidity may often develop before diagnosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…2 Glycated hemoglobin (HbA1c) has been used as a clinical diagnostic marker of relatively long-term ($90 days) glucose control in diabetic patients. 3 However, the Maillard reaction, and AGEs in general, are believed to play a more pathogenic role in the development of atherosclerosis and diabetic complications. The Maillard hypothesis of diabetic complications proposes that chronic, cumulative chemical modification of proteins by glycation and AGEs alters their turnover, structure, and function.…”
mentioning
confidence: 99%